1991
DOI: 10.1002/jcp.1041490103
|View full text |Cite
|
Sign up to set email alerts
|

The level of substrate ornithine can alter polyamine‐dependent DNA synthesis following phorbolester stimulation of cultured hepatoma cells

Abstract: Although the precise intracellular function(s) of the polyamines remain incompletely defined, a myraid of evidence now shows that the polyamines must accumulate or be maintained at a specific intracellular concentration in order for all mammalian cells to grow or divide. The initial step in polyamine biosynthesis normally involves the decarboxylation of ornithine by the enzyme ornithine decarboxylase (ODCase E.C. 4.1.1.17) to yield putrescine. Increases in the steady-state level of intracellular ornithine have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…A similar result was described by Byus and Wu [19] . They investigated human hepatoma cells (H35) and showed a promotion of proliferation by incubation with 0.5 m M L -ornithine.…”
Section: L-ornithine-mediated Effects On the Expression Of Arginasesupporting
confidence: 76%
“…A similar result was described by Byus and Wu [19] . They investigated human hepatoma cells (H35) and showed a promotion of proliferation by incubation with 0.5 m M L -ornithine.…”
Section: L-ornithine-mediated Effects On the Expression Of Arginasesupporting
confidence: 76%
“…In the period between hatching and the first feeding, there is a decrease of polyamines. The ornithine concentration can be sufficient to supply polyamine synthesis during the development, since the maintenance of the cell polyamine concentration for growing, proliferation (Pilz et al 1990) and DNA synthesis is dependent on it and is altered by the concentration of its precursor, ornithine (Byus and Wu 1991). The ODC gene is housekeeping, and the putrescine production is regulated by polyamine levels in the ODC translation (Matsufuji et al 1996, Saito et al 2000.…”
Section: Discussionmentioning
confidence: 98%
“…Besides, many validated target genes of miRNA-122 are involved in cell proliferation (Tsai et al, 2009). Particularly, CAT-1 is responsible for the transport of the cationic amino acids, and this intake stimulates DNA synthesis for cell replication (Byus and Wu, 1991). Cyclin G1, on the other hand, modulates the G2/M transition of the cell cycle, and experimental evidences obtained in cancer cell lines and tumor xenograft have shown that suppression of Cyclin G1 reduces cell proliferation and induces apoptosis, which leads to the inhibition of tumor growth (Chen et al, 1997;Gordon et al, 2000).…”
Section: Discussionmentioning
confidence: 99%